1987
DOI: 10.3354/meps038217
|View full text |Cite
|
Sign up to set email alerts
|

Feeding behavior and morphological adaptations in two sympatric sea urchin species in central Chile

Abstract: ABSTRACT. Loxechinus albus and Tetrapygu niger are 2 sympatric sea urchin species present in the rocky intertidal and subtidal zones of central Chile. In this study we test the hypothesis that the 2 species employ dfferent feeding mechanisms, and that this has resulted in distinct ecological roles for the 2 species. We also analyze structures associated with feeding. Results from field studies indicate that T niger principally consumes benthic algae (i.e. Gelidium spp.) and in doing so clears significantly mor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
29
0
2

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(35 citation statements)
references
References 8 publications
(11 reference statements)
2
29
0
2
Order By: Relevance
“…These results are consistent with a hypothesis of enlarged lantern size being a functional specialization for durophagy, and is apparently the first evidence of a relationship between trophic morphology and diet in regular sea urchins. The hypothesis that enlarged lantern size is an adaptation for durophagy is also consistent with studies of sympatric sea urchins from different genera, where the species with the largest lantern occupies microhabitats with a scarcity of soft food (Contreras and Castilla 1987;Fernandez and Boudouresque 1997). However, contrary to the assumption of a direct relationship between lantern size and feeding capacity in strongylocentrotid sea urchins (Lawrence et al 1995), there was also a large inter-specific difference in feeding capacity The slope and elevation of the logarithmic allometric equation, ln(Y) = ln(a) + bln(X), were determined using standardized major axis (SMA) estimation.…”
Section: Enlarged Lantern Size and Durophagysupporting
confidence: 72%
“…These results are consistent with a hypothesis of enlarged lantern size being a functional specialization for durophagy, and is apparently the first evidence of a relationship between trophic morphology and diet in regular sea urchins. The hypothesis that enlarged lantern size is an adaptation for durophagy is also consistent with studies of sympatric sea urchins from different genera, where the species with the largest lantern occupies microhabitats with a scarcity of soft food (Contreras and Castilla 1987;Fernandez and Boudouresque 1997). However, contrary to the assumption of a direct relationship between lantern size and feeding capacity in strongylocentrotid sea urchins (Lawrence et al 1995), there was also a large inter-specific difference in feeding capacity The slope and elevation of the logarithmic allometric equation, ln(Y) = ln(a) + bln(X), were determined using standardized major axis (SMA) estimation.…”
Section: Enlarged Lantern Size and Durophagysupporting
confidence: 72%
“…(percent wet weight (g)) at the end of the experiment. Factors include: "Urchin" (Ur; three levels: P. lividus, A. lixula and no urchins), fixed, and "Aquarium" (Aq; three levels), random and nested in Ur (n ¼ 3 and/or sessile invertebrates from hard substrata by means of the powerful teeth of the Aristotle's lantern, and (3) capture of drift algae, 'drift-trapping behaviour', by the ambulacral tube feet and spines and the subsequent transport of this material to the mouth (Conteras and Castilla, 1987;Lawrence, 2013). Regarding this, the two urchin species differ morphologically: P. lividus has shorter and denser spines, more extendible aboral tube feet and a weaker Aristotle's lantern than A. lixula and it is likely that such differences affect their feeding behaviors Flammang, 2005, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have considered this species unable to use drift algae as an important food item (Vásquez 1986, Contreras & Castilla 1987, although this could be partly overcome by aggregation, i.e. formation of highdensity groups in zones with strong bottom currents (Vásquez & Buschmann 1997).…”
Section: Arrival Patterns Of Drift Kelp and Availability To Sea Urchinsmentioning
confidence: 99%
“…This urchin mainly consumes turfing algae (Contreras & Castilla 1987). Moreover, it has been considered unable to use drift algae as an important food item because it lacks the morphological structures necessary to capture this kind of resource (Vásquez 1986, Contreras & Castilla 1987. Vásquez (1993) has, however, suggested that this morphological deficiency could be overcome, in part, through the aggregation of individuals, which increases the probability of retaining drift material among spines.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation